Conflict in the wage-led growth model - Romar Correa (Kiel Institute for the World Economy (IfW), 2014)
We model the interaction between capitalists and entrepreneurs as a dynamic game. The open-loop Nash equilibrium and the closed-loop Nash equilibrium are distinguished. The elasticity of intertemporal substitution as well as the level and responsiveness of the wage rate to the accumulation of capital are shown to be important for wage-led growth.
Keywords: B51; C73; 330; capital accumulation; conflict: cooperation